PROVIDING OF FIRE-RESISTANCE OF THE EXPLOITED STEEL CONSTRUCTIONS (Collection of scientific works «Modern structures of metal and wood», 2020)
The  modern state of the question  is generalized, the tasks of researches are put, basic pre-conditions of application of defence of on-the-road steel build constructions are marked from  high  temperature  influences.  The  review  of  results  of  researches  of  different  aspects  of defence  of  constructions  is  resulted,  determinations  of  the  technical  state  in  the  process  of exploitation  after  different  influences  and  its  adjusting  by  repair,  strengthening  or  replacement. Works of the known scientists in this area, in which positions of theory of calculation of building constructions  are  expounded  taking  into  account  high  temperature  influences,  are  analysed.  The analysis of existent methods allowed to set that the methods of calculation of steel constructions, estimations of their technical state and ground of possibility of subsequent reliable exploitation of constructions of buildings and buildings, taken to the practical use absent after different influences.  Procedure of planning, device and estimation of fire-resistance of steel constructions  in the process of exploitation is offered.  The method of research of the technical state of steel constructions, damaged as a result of fire is  resulted.  During  implementation  of  works  a  hearth  and  reasons  of  fire,  size  of  maximal temperature at a fire, areas of thermal damages, is set, duration of heating in the different areas of fire etc. On the basis of findings a conclusion prepares about the technical state of constructions and possibility or impossibility of proceeding in their service ability.  In accordance with requirements it is recommended to determine the criteria of estimation of the  technical  state  and  fire-resistance  of  material  and  constructions  a  project  and  normative document on the whole.  The method of receipt of determining parameters of the technical state and fire-resistance of steel constructions is developed and approved. It is foreseen, that constructions and elements during all of life cycle as a result of senescence, degradation and other influences can consistently be in each of four technical states.  The  results  of  estimation  of  the  technical  state  and  fire-resistance  of  constructions  of  the buildings, which got damage as a result of exploitation of both fire and measure on adjusting of the technical state and fire-resistance of constructions are presented.